Commercial process for the recovery of metals from ITO etching industry wastewater by liquid–liquid extraction: simulation, analysis of mechanism, and mathematical model to predict optimum operational conditions1. Issue 7 (6th July 2015) - Swain, Basudev; Mishra, Chinmayee; Hong, Hyun Seon; Cho, Sung-Soo; Lee, Sung kyu
<x xml:space="preserve">Abstract</x> A commercial process for the recovery of metals from the indium-tin-oxide (ITO) etching industry wastewater by liquid–liquid extraction has been developed.